2022
DOI: 10.3389/fpsyg.2022.1006007
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exercise intention and behavior of Chinese college students: A moderated mediation model

Abstract: Inconsistency between intention and behavior is very common in daily life. This study explored the intention-behavior relationship in exercise, focusing on the mediating effect of action planning and the moderating effects of habit strength and gender. For the purpose of providing theoretical reference for the implementation of intervention strategies in the volitional phase, a total of 489 college students (M-age = 20.61, 57.46% female) from Hubei Province, China, were recruited to complete the questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The higher the score, the higher the meaning of life of the subjects. Studies have shown that the scale has good reliability and validity among Chinese college students (Zhu et al, 2022). In this study, the Cronbach α coefficient of the scale was 0.945.…”
Section: Meaning In Lifementioning
confidence: 49%
“…The higher the score, the higher the meaning of life of the subjects. Studies have shown that the scale has good reliability and validity among Chinese college students (Zhu et al, 2022). In this study, the Cronbach α coefficient of the scale was 0.945.…”
Section: Meaning In Lifementioning
confidence: 49%
“…Prior research has demonstrated the satisfactory validity and reliability of scale among Chinese college students. 6 In this study, the Cronbach's α for the scale was 0.78.…”
Section: Bedtime Procrastination Scale (Bps)mentioning
confidence: 56%
“…4 Research evidence has indicated that bedtime procrastination is related to many negative health conditions, such as sleep insufficiency, poor sleep quality, high levels of daytime fatigue and sleepiness. 5 , 6 Thus, given the links between bedtime procrastination and these adverse consequences, it is vital to examine the predictors of bedtime procrastination and possible mechanisms to inform a more holistic physical and mental health intervention and promotion approach for college students.…”
Section: Introductionmentioning
confidence: 99%
“…During their university years, individuals often have more flexible schedules, but a lack of guidance and supervision in aspects of healthy living can lead to variable sleep patterns and irregular routines, negatively impacting sleep quality ( 8 , 41 ). The prevalence of staying up late and nocturnal activities among college students further affects their sleep quality ( 42 ). Lower sleep quality fails to alleviate negative emotions in college students, resulting in weaker subjective well-being.…”
Section: Discussionmentioning
confidence: 99%